Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1063/1.3364132
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of conductive interconnects by Ag migration in Cu–Ag core-shell nanoparticles

Abstract: Fabrication of conductive nanoparticle films is observed in Cu–Ag core-shell nanoparticles by fast diffusion of Ag at 220 °C from particle surfaces, leading to the formation of sintered necks of Ag at the initial particle-particle contacts. Transmission electron microscopy showed that the necks were pure Ag and that particle surfaces away from the contacts were nearly Ag-free. The extent of neck formation is controllable by the choice of initial Ag thickness. Analysis of the thermodynamics of the Ag–Cu system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 17 publications
0
59
0
Order By: Relevance
“…After sintering, the joint can operate at 350°C with a corresponding homologous temperature of only 0.5. Nanoparticle sintering for high power and high temperature die attach applications have been previously reported using Ag NPs [6,8,[12][13][14][15] while sintering using Cu NPs have also been reported [16][17][18][19] although these typically require applied pressure, UV light or a reducing atmosphere for successful sintering. The present work reports on changes in shear strength and the corresponding evolution of voids and grain boundaries when a commercially available Ag NP paste is used to bond Si test die to a ceramic package with Ni/Au surface metallization, followed by storage at 300°C.…”
Section: Introductionmentioning
confidence: 99%
“…After sintering, the joint can operate at 350°C with a corresponding homologous temperature of only 0.5. Nanoparticle sintering for high power and high temperature die attach applications have been previously reported using Ag NPs [6,8,[12][13][14][15] while sintering using Cu NPs have also been reported [16][17][18][19] although these typically require applied pressure, UV light or a reducing atmosphere for successful sintering. The present work reports on changes in shear strength and the corresponding evolution of voids and grain boundaries when a commercially available Ag NP paste is used to bond Si test die to a ceramic package with Ni/Au surface metallization, followed by storage at 300°C.…”
Section: Introductionmentioning
confidence: 99%
“…For example, AgCo nanoalloys have been employed in the oxygen reduction in alkaline media 37 , and AgCu clusters are proposed as more efficient catalysts than the corresponding pure clusters for oxygen reduction reactions 33 . AgCu nanoalloys find application in the fabrication of Pb-free solder interconnects, that can melt at low temperatures 38 . Core-shell Au-Co nanoparticles have been proposed also for biomedical applications, such as thermal ablation therapies and drug delivery, for which the magnetic Co core is coated by a shell of Au, which is a biocompatible material that can be easily functionalized [39][40][41] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various studies on sintering of Ag nanoparticles paste for bonding have been reported [1][2][3][4][5][6][7][8][9]. However, the application of Ag nanoparticles paste is still restricted by long sintering time which is about 20-30 min [1,[3][4][5][6][7] and high sintering temperature which is normally above 250 °C [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 97%